Mode-locked L-band bismuth–erbium fiber laser using carbon nanotubes - Ahmad, Harith; Zulkifli, Ahmad Zarif; Muhammad, F.D.; Zulkifli, M.Z.; Thambiratnam, K.; Harun, Sulaiman Wadi (Springer, 2014)
A passively mode-locked, bismuth–erbium-co-doped fiber (Bi-EDF) with a pulse width of 460 fs is proposed and demonstrated. A highly doped, 180-cm Bi-EDF with an erbium concentration of 3,250 ppm/wt and an absorption rate of 133 dB/m at 1,530 nm serves as the gain medium. The cavity is 11.6 m long with an overall group velocity dispersion of +0.063 ps2. The output pulses have a repetition rate, average output power, pulse energy and peak power of 11.18 MHz, 5 mW, 448 pJ and 1 kW, respectively. The system has a high beam quality and a narrow pulse width output in the L-band region.